The Effect of ROA, ROE, CR, DER and EVA on Stock Return of Non-Banking Companies Listed on the Lq-45 Index and Sri-Kehati Index on the Indonesia Stock Exchange 2015-2019 - Herry Santoso; Gracia Shinta S. Ugut (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The purpose of this study is to assess empirically on the influence of financial ratios consisting of Return on Assets (ROA), Return on Equity (ROE), Current Ratio (CR), Debt to Equity Ratio (DER) and Economic Value Added (EVA) ) on Stock Return. The data used in this study is secondary data. The sample for this study chosen is purposive sampling with the purpose of obtaining the sample based on criteria. Sample for this study is non-banking companies from 39 companies registered in LQ-45 Index and 20 registered in Sri-Kehati Index in Indonesian Stock Exchange from the year 2015 to 2019. Of 20 companies in Sri-Kehati Index, 13 companies are also part of LQ-45 Index, therefore the total overall samples taken are 46 non-banking companies. The analysis model used for this study is multiple linear regression. The result of study indicated that ROA and EVA have positive influences on stock returns, but ROE and CR have negative influences. While for DER, it has no influence on stock return.